PARENT’S STRATEGY TO ATTRACT CHILDREN TO EAT, FEEDING DURATION, AND ITS RELATION TO WEIGHT FOR AGE Z-SCORE IN CHILDREN - Masayu Ramadhani Polanunu; Nanda Hudawarrahmah; Hartojo Hartojo; Meta Herdiana Hanindita; Nur Aisiyah Wijaya; Siti Nurul Hidayati; Roedi Irawan; Boerhan Hidajat (Media Gizi Indonesia, 2020)
Appropriate feeding practices are critical for gaining and maintaining nutrition and development in children. Previous study in feeding practices indicated that inappropriateness in feeding practices had consequences in children’s growth and development. This study aimed to determine corelation between parents strategy to attract children to eat and feeding duration to weight for age z-score in children. This was a simple random sampling, cross-sectional study and held on April to June 2016 in Dr. Soetomo Hospital and Husada Utama Hospital, Surabaya, Indonesia. Subjects in this study were children from 6 to 24 months. Feeding practice determined by interview with children’s parents which consisted parent’s strategy to attract children to eat, feeding duration, and then children were measured weight for age z-score using WHO chart. Statistical analysis used Spearman correlation test. Thirty children were enrolled, 50% were male, with median age 16.5 months (6-24 months). Parents strategy to attract children to eat (53.3% talking, 30% playing and 16.7% watching television) had correlated signifi cantly with weight for age (r= 0.35, p= 0.028). Meanwhile, 56.7% children with feeding duration more than 30 minutes and 43.3% children with time feeding duration less than 30 minutes. Feeding duration had no correlation with weight for age in children (r=-0.32, p=0.43). We conclude from this study that parents strategy to attract children to eat had signifi cant correlation to weight for age but feeding duration had no correlation with weight for age. This study implied that strategy to attract children to eat is necessity in children physical development. Meanwhile, feeding duration has no signifi cant implication. We recommended children must be persuaded as part of parents strategy in order to attract them to eat.